Abhik Gupta, "Many Layers of Ecocentrism" - Penumala, Pratap Kumar (Journal for the study of religion, nature and culture, 2025)
Abhik Gupta, Many Layers of Ecocentrism (London, New York: Routledge, 2024), 248 pp., £ 40 (pbk), ISNB: 9781032770765.